Sex differences in medial prefrontal and parietal cortex structure in children with disruptive behavior. (February 2021) - Ibrahim, Karim; Kalvin, Carla; Li, Fangyong; He, George; Pelphrey, Kevin A.; McCarthy, Gregory; Sukhodolsky, Denis G.
Graphical abstract: Highlights: The relationship between sex differences in brain structure and disruptive behavior in children remains poorly understood. Reduced gray matter volume was found in the left vmPFC for boys with disruptive behavior, but not in girls. Reduced cortical thickness was found in the left supramarginal gyrus for boys with disruptive behavior, but not in girls. Sex-specific associations were found between disruptive behavior severity and brain structure. These findings have implications for identifying biomarkers that can inform target-based treatments. Abstract: Sex differences in brain structure in children with disruptive behavior disorders (DBD) remain poorly understood. This study examined sex differences in gray matter volume in children with DBD in a priori regions-of-interest implicated in the pathophysiology of disruptive behavior. We then conducted a whole-brain analysis of cortical thickness to examine sex differences in regions not included in our hypothesis. Exploratory analyses investigated unique associations between structure, and dimensional measures of severity of disruptive behavior and callous-unemotional traits. This cross-sectional study included 88 children with DBD (30 females) aged 8–16 years and 50 healthy controls (20 females). Structural MRI data were analyzed using surface-based morphometry to test for interactions between sex and group. Multiple-regression analyses tested for sex-specific associations between structure, callous-unemotional traits, and disruptive behavior severity. Boys with DBD showed reduced gray matter volume in the left ventromedial prefrontal cortex (vmPFC) and reduced cortical thickness in the supramarginal gyrus, but not girls compared to respective controls. Dimensional analyses revealed associations between sex, callous-unemotional traits, and disruptive behavior for amygdala and vmPFC volume, and ventrolateral prefrontal cortex cortical thickness. Sex-specific differences in prefrontal structures involved in emotion regulation may support identification of neural biomarkers of disruptive behavior to inform target-based treatments.